(untitled) (Sains Humanika, 2007)
Education in Malaysia is fast becoming a â€œwired enterprise.â€ The integration of Information and Communication Technology (ICT) in course offerings in institutions of higher learning (IHL) is seen as the catalyst towards producing lifelong autonomous learners. Hence, Computerâ€“Mediated Communication (CMC) is seen as the tool to assist learners in acquiring information at their fingertips anywhere and anytime. This paper employed a descriptive research methodology to investigate learner autonomy via an online distanceâ€“learning program. The research instruments used included survey questionnaires, semiâ€“structured interview protocols and email interactions. The sample population for this study entailed purposive sampling where one intact class of first year students pursuing the B. Ed. (TESL) course in a local university offering online distance learning was selected. Initial findings indicated that first year university students generally, did not consider themselves to be truly independent learners capable of managing their own learning. In fact, their responses in all aspects of learner autonomy abilities viz. planning, organizing, monitoring, evaluating and computer usage recorded moderately positive responses. In lieu of this, if todayâ€™s tertiary students are required to participate through CMC, it is the responsibility of educators and IHL to systematically guide and provide learners the skills, tools, attitude and knowledge through learner training programs on how they can learn to take responsibility for their own learning.